Pelatihan Pembuatan Noken Pada Ibu-Ibu Asli Papua di Kelurahan Fandoi - Iriawan, Hermanu; Hasim, Djamil; Haz, Musdalifah (Abdi Masyarakat, 2023)
Noken making training for Papuan mothers in Fandoi Village aims to introduce and improve skills in making traditional woven noken. The implementation method used is a direct and participatory practice approach. The training begins with a demonstration session, where instructors who are proficient in noken making show the basic steps firsthand. After that, participants are given the opportunity to do hands-on practice with the guidance of instructors. During the training, there were also discussion and question and answer sessions to provide a deeper understanding of weaving techniques and material selection. In addition, participants are also grouped in small teams to work together on noken making, encouraging collaboration and mutual assistance. This training is expected to provide benefits in preserving the culture of woven noken and improving the skills and welfare of Papuan mothers in Fandoi Village.